(untitled) (Journal of Digital System Development, 2024)
In today’s fast-paced and connected world, membership management systems are essential for clubs, associations, non-profits, and sports teams to streamline operations and enhance member experiences. The requirement for a membership management system arises due to the challenge of efficiently managing many members. As organisations grow and diversity, traditional manual record keeping and event management methods become impractical and error-prone. A membership management system offers a comprehensive and automated solution to handle membership-related tasks effectively. This paper aims to develop a system that provides an intuitive and user-friendly experience for administrators and members, enabling them to manage their profiles seamlessly, access personalised services, and participate in various activities. Also, it can streamline administrative processes, automate manual tasks, and centralise data to enhance association efficiency. By simplifying these aspects, associations can focus on strategic initiatives and foster more robust engagement within their community. A usability evaluation was conducted on 32 respondents. During the testing phase, participants explored the application and interacted with the website, testing its features, usability, ease of use and functionality. The evaluation findings show a positive outcome for the membership management system, with users expressing high satisfaction and providing positive feedback about the website’s usability, ease of use, and functionality.